PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL PROJECT ECOPRINT PADA KURIKULUM MERDEKA SEKOLAH DASAR - Zefitri, Yeni; Hakim, Lukman; Faipri Selegi, Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was carried out at SD Negeri 231 Palembang for the 2023/2024 school year. The type of research carried out to produce or obtain media and use ADDIE research and development procedures which have five stages, namely Analysis, Design, Development, Implementation and Evaluation. Initial analysis from problem discovery to collecting supporting materials such as teaching modules, design, designing media displays according to what is desired, development, collection of materials and tools to make video tutorial media products for the Ecoprint project, implementation of combining media obtained and adapted into video learning media. ecoprint project tutorial, and trial evaluation including validation by PGRI University Palembang lecturers as media and material experts. And also this ecoprint project video tutorial is very helpful in the process of making ecoprints.